Views of Turkish people on oocyte and sperm donation - DEMİRGÖZ BAL, MELTEM (CUKUROVA UNIV, FAC MEDICINE, 2019)
Purpose: The aim of the study is to determine the views of the Turkish people on oocyte/sperm donation. Materials and Methods: Following informed consent, a questionnaire was given to women and their spouses who presented to obstetrics and gynecology outpatient clinics of a university hospital. The data collection form consists of 35 questions about the demographics of the participants and their thoughts about oocyte/sperm donation. A total of 428 women, including 323 women and 105 men, agreed to participate in the sampling study. Results Sixty-four-point three percent of the women and 71.4% of males found use of donated oocytes/sperms in infertile couples unacceptable. Sixty-three-point one percent of the participants said that both couples receiving, and those donating oocytes/sperms should get counseling. Twenty-one point-five percent of the participants approved of infertile couples' receiving oocytes/sperms donated by their relatives (e.g. sister) and friends and 31,8% agreed about getting them from strangers. Eighty-eight-point seven percent of the primary school graduates, 73.4% of the university graduates and postgraduates, 76.7% of the employed participants, 86.2% of the participants with an income lower than their expenses and 85.1% of the participants with live children reported to unaccept donated sperms if their spouses had a problem preventing them from having a child. Conclusion: More than half of the participants declared that it was not appropriate to have children through infertile-donated oocyte/sperm.
Keywords: oocyt; sperm; donation; gametI; ASSISTED REPRODUCTIVE TECHNOLOGIES; PUBLIC PERCEPTIONS; GAMETE DONATION; EGG DONATION; INFERTILITY; ATTITUDES; CONCEPTION; OPINION; WOMEN; IRAN